MTF1 binds to metal‐responsive element e within the ATP7B promoter and is a strong candidate in regulating the ATP7B expression. (9th October 2019) - Stalke, Amelie; Pfister, Eva‐Doreen; Baumann, Ulrich; Illig, Thomas; Reischl, Eva; Sandbothe, Maria; Vajen, Beate; Huge, Nicole; Schlegelberger, Brigitte; von Neuhoff, Nils; Skawran, Britta
Abstract: Wilson's disease is an autosomal recessive disorder resulting from copper excess. Some patients with clinical Wilson's disease symptoms exhibit no or only heterozygous pathogenic variants in the coding region of the disease‐causing ATP7B gene. Therefore, the ATP7B promoter region is of special interest. Metal‐responsive elements (MREs) located in the ATP7B promoter are promising motifs in modulating the ATP7B expression. We studied protein interaction of MREe, MREc, and MREd by electrophoretic mobility shift assays and revealed specific interactions for all MREs. We further narrowed down the specific binding site. Proteins potentially binding to the three MREs were identified by MatInspector analyses. Metal regulatory transcription factor 1 (MTF1) could be validated to bind to MREe by electrophoretic mobility shift assays. ATP7B promoter‐driven reporter gene expression was significantly increased because of this interaction. MTF1 is a strong candidate in regulating the ATP7B expression through MREe binding.